Economic Evaluations of HPV Vaccination in Targeted Regions of Low- and Middle-Income Countries: A Systematic Review of Modelling Studies - Frianto D; Setiawan D; Diantini A; Suwantika AA (Dove Medical Press, 2022)
Dedy Frianto,1,2 Didik Setiawan,3 Ajeng Diantini,1,4 Auliya A Suwantika1,4 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Bandung, Indonesia; 2Faculty of Pharmacy, Universitas Buana Perjuangan, Karawang, Indonesia; 3Faculty of Pharmacy, Universitas Muhammadiyah Purwokerto, Purwokerto, Indonesia; 4Center of Excellence in Higher Education for Pharmaceutical Care Innovation, Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Auliya A Suwantika, Faculty of Pharmacy, Universitas Padjadjaran, Jl. Raya Bandung-Sumedang Km. 21, Jatinangor, Sumedang, 45363, Indonesia, Email auliya@unpad.ac.idBackground: In countries with limited resources, a targeted HPV vaccination strategy by focusing in selected regions is preferable to be implemented than a nationwide vaccination strategy.Objective: This study aimed to review articles on economic evaluations of HPV vaccination in countries over the world that applied targeted vaccination strategies.Methods: Approximately 1769 articles were obtained from two databases (1242 and 527 articles from PubMed and ProQuest, respectively). The inclusion criteria in this systematic review were studies about full economic evaluations of HPV vaccination in targeted area or sub-national level and written in English. Full-text screening was applied to evaluate the eligibility. Final articles obtained were referred to the Consolidated Health Economic Evaluation Reporting Standard (CHEERS) checklist. Finally, we included only 4 articles that met all inclusion and exclusion criteria.Results: Included studies in this review focused in different targeted regions, such as Punjab State in India, Vientiane in Lao PDR, Southern Vietnam in Vietnam, and Brazilian Amazon in Brazil. From 24 criteria in the CHEERS checklist, all included studies could meet 21 criteria (87.5%). All included studies in this review applied modeling approaches, which can estimate the number of cases and treatment costs averted. Applying various settings, the results of this study showed that HPV vaccination could potentially reduce the number of cervical cancer cases by 20- 72%. Taking cervical cancer screening into account, this study showed that targeted HPV vaccination was cost-effective or even cost-saving.Conclusion: Implementation of HPV vaccination in sub-national level as the initial step before nationwide vaccination is more favorable to be implemented in countries with limited budget.Keywords: cost-effectiveness, cervical cancer, vaccine, immunization, screening